Household Food Expenditure Typology and Its Association with Child Stunting and Anemia in Indonesia - Sartika, Ratu Ayu Dewi; Yusnita, Yusnita; Ningsih, Winda M; Wulandari, Ririn Arminsih; Pujonarti, Siti A; Wirawan, Fadila (Kesmas, 2024)
Stunting and anemia remain the coexisting nutritional problems among Indonesian children. However, evidence of household-level food expenditure and its association with child stunting and anemia is limited. This study aimed to observe the association between household food expenditure typology and child stunting and anemia in Indonesia. Data was obtained from the 2007 and 2014 Indonesia Family Life Survey (IFLS). The household food expenditure, child nutritional status, and anemia were observed in 2007 and 2014. Latent class analysis was taken to identify the food expenditure pattern. Binary logistic regression was applied to analyze the association between household food expenditure patterns and stunting and anemia status. A total of 2,296 children from 2,158 households were included in the study. Household food expenditure was identified into (1) higher processed food, refined grain, and purchased meals; (2) higher fish, seafood, plant protein, vegetables, and beans; and (3) balanced food purchases. Households with Pattern 2 had lower odds of anemia in 12–59-month-olds than Pattern 3 (AOR 0.78, p-value = 0.03, 95% CI). Households with Pattern 2 were likely to have stunted 8–12-year-olds compared to households with Pattern 3 (AOR 1.37, p-value = 0.09, 95% CI). Household food expenditure types may affect children’s nutritional status.